An efficient pH‐responsive kappa‐carrageenan/tamarind kernel powder hydrogel for the removal of brilliant green and rose bengal from aqueous solution. Issue 21 (3rd February 2022) - Vaid, Vasudha; Jindal, Rajeev
Abstract: The objective of this study was to develop an eco‐friendly, cost‐effective, and efficient adsorbent using kappa‐carrageenan (KCG) and tamarind kernel powder (TKP) based cross‐linked 3‐D network hydrogel. The equilibrium swelling capacity of 1429% was achieved by optimization studies. The KCG/TKP hydrogel was characterized by Fourier transform infrared spectroscopy, X‐ray diffraction, field emission scanning electron microscopy, energy dispersive spectroscopy, and thermogravimetric analysis. This hydrogel was employed for the efficient removal of brilliant green (BG) and rose bengal (RB) dye from wastewater. BG and RB were used as a cationic and anionic model dye, respectively. The adsorption capacity of model dyes on KCG/TKP was investigated under different parameters like dye concentration, pH, temperature, and adsorbent amount. With remarkable adsorption capacity, the hydrogel demonstrated a strong dependence on the pH of the medium. The kinetics, adsorption isotherm, thermodynamic studies, and reusability were investigated. The KCG/TKP hydrogel follows pseudo‐second‐order kinetics and the Langmuir isotherm model for the adsorption of both BG and RB model dyes. Spontaneity and exothermic behavior of the adsorption process were revealed by thermodynamic findings. At pH 9, the maximum adsorption capacity of BG was 840.33 mg g −1 while the maximum adsorption capacity of RB was 168.06 mg g −1 at pH 5. Abstract :